STRATEGI CERDAS DAN AMAN MENGGUNAKAN MEDIA SOSIAL BAGI GENERASI X DAN Z - Aribia Razzina Ainun Nisa; Rafif, Muhammad; Maria Yuniati Baolifa Betore Kerans; Yulanda Athina Zahra; Pangestu Adi Prasetio; Siti Chonisatul Fatimah; Arif Murti Rozamuri (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Technological advancements have brought significant positive impacts to daily life, but they have also posed new challenges, particularly concerning the rising cases of online fraud targeting Generations X and Z. This article highlights the main issue at hand: the lack of knowledge and awareness among these groups, making them susceptible to financial and psychological losses due to online fraud and scams. In response to this issue, the workshop "Smart and Safe Use of Social Media" was held in Kramat Jati, aimed at raising awareness about online fraud and providing practical protection strategies to participants. The training methodology involved selective respondent selection, using appropriate tools for training and evaluation, and systematically collecting and analyzing data to assess workshop effectiveness. Targeted specifically at PKK mothers, the workshop resulted in improved understanding among participants regarding the identification of various online scams, awareness of data theft threats, and the implementation of effective preventive measures to protect themselves and their families. Participants gained valuable knowledge and practical skills empowering them to navigate the digital world more safely and confidently. This workshop successfully made a positive impact by enhancing digital literacy and reducing vulnerability to online fraud among Generations X and Z.